Geographic patterns of skull variation in two species of cavies of the genus microcavia (Rodentia, caviidae) - D'hiriart, Sofia (2021)
We study the geographical variation of the skull in the cavies Microcavia australis and M. maenas and its association with environmental variables. We tested four hypotheses previously proposed to explain the geographic patterns of morphological variation i) heat conservation; ii) heat dissipation; iii) primary productivity and iv) seasonality. We used 16 cranial measurements taken from 180 individuals. We analyzed the spatial variation in cranial morphology through Generalized Additive Models. Both species showed a north-south clinal gradient in skull size (increasing towards colder, less seasonal environments, with lower summer rainfalls in M. australis and towards warmer and seasonal environments in M. maenas). Microcavia australis presented greater ecomorphological variability than M. maenas, in agreement with its wider distribution and occurrence in more diverse environments. Also, the length of tympanic bullae in M. australis was larger towards its northern distributional range (associated to smaller skulls), and smaller to the south (associated to larger skulls). Overall, the distributional range of both species coincided with unproductive environments, where temperature represents a limiting factor and, together with rainfall, might determine the observed morphological patterns.